2020
DOI: 10.5539/jas.v12n3p78
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Agricultural Credit Access on Rice Productivity: Evidence from the Irrigated Area of Anambe Basin, Senegal

Abstract: Rice is an important staple food in many developing countries, especially in Senegal. However, rice production in Senegal only meet 20% of the domestic demand largely due to the poor performance of rice farmers and low productivity. Access to agricultural credit has strong impacts on the technical efficiency of farmers and would promote inputs and new technology adoption. But that is not clear enough in previous studies. This study investigates the impact of agricultural credit access on rice productivity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Similarly, the findings of other studies related to India also support the present study's findings (Manoharan and Varkey, 2021;Misra et al, 2016;Naidu et al, 2013;Shivaswamy et al, 2020). Further, findings are also observed in other countries around the globe, such as Senegal (Diallo et al, 2020), Togo (Agbodji and Johnson, 2021), Indonesia (Wicaksono, 2014), and Pakistan (Khan et al, 2013;Hussain and Taqi, 2014;Kashif et al, 2016).…”
Section: Long and Short-run Elasticitiessupporting
confidence: 92%
See 3 more Smart Citations
“…Similarly, the findings of other studies related to India also support the present study's findings (Manoharan and Varkey, 2021;Misra et al, 2016;Naidu et al, 2013;Shivaswamy et al, 2020). Further, findings are also observed in other countries around the globe, such as Senegal (Diallo et al, 2020), Togo (Agbodji and Johnson, 2021), Indonesia (Wicaksono, 2014), and Pakistan (Khan et al, 2013;Hussain and Taqi, 2014;Kashif et al, 2016).…”
Section: Long and Short-run Elasticitiessupporting
confidence: 92%
“…In the global context, Diallo et al. (2020) conducted a study on the impact of agricultural credit on rice yield during June and July 2019 in the Anambe basin of Senegal. Their study used stochastic frontier analysis and found that agricultural credit positively affects rice yield.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the FGT revealed a high rate of poverty among cassava farmers (66.7%), with a higher incidence in those without access to credit. Diallo et al (2020) used Stochastic Frontier Analysis (SFA) to estimate the effect of agricultural credit on rice farmers' productivity and efficiency. They found that the effects of access to agricultural credit, gender, education, ethnicity, use of improved seeds, and land tenure system on the technical inefficiency of rice production are significant.…”
Section: Introductionmentioning
confidence: 99%